1986
DOI: 10.1002/j.2162-6057.1986.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Ideation Principle of Extended Effort in Real World Professional and Managerial Creative Problem Solving*

Abstract: Two hypotheses relating to using the ideation principle of extended effort in idea generation to solve real world technical and managerial problems are tested in field research. In two studies involving training and application of a "complete process of creative problem solving" emphasizing the ideation-evaluation process, the "most preferred ideas" were well dispersed and furthermore were more likely to be found among the latter two thirds of the ideas listed serially than in the first third. This provides su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…The tendency of novel combinations increasing with time supports Hypothesis 4, is consistent with Kohn and Smith (in press), and matches other findings that creative outputs increase over time (Basadur & Thompson, 1986;Ward, Sifonis, & Wilkenfeld, 1996). The pattern of findings from the combination process is similar to that of prior research on computer based idea generation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The tendency of novel combinations increasing with time supports Hypothesis 4, is consistent with Kohn and Smith (in press), and matches other findings that creative outputs increase over time (Basadur & Thompson, 1986;Ward, Sifonis, & Wilkenfeld, 1996). The pattern of findings from the combination process is similar to that of prior research on computer based idea generation.…”
Section: Discussionsupporting
confidence: 87%
“…The combination process should also vary over time. One would expect more novel combinations over the course of a combination session, as is the case in regular brainstorming (Basadur & Thompson, 1986;Parnes, 1961). The most easily accessible and thus more common ideas should be tapped in the early phase of the idea search process (Paulus & Brown, 2003).…”
mentioning
confidence: 99%
“…The latter did not, however, use problems that the participants were familiar with or committed to, and the duration of the training was much shorter than that of the former study. Basadur and Thompson (1986) demonstrated that, for both individuals and groups, on real world technical professional problems, training produced results consistent with the paradigms established in the laboratory by Meadow (1959, 1960). Other support of the value of creative problem solving techniques includes Rickards and Carson (1979) and Gryskiewicz (1987).…”
supporting
confidence: 76%
“…According to Osborn (1953) quantity breeds quality in ideation and early ideas are unlikely to be of higher quality during an ideation session. The rationale for the measure quantity is that generating a large number of ideas enhances the chance of better ideas (Osborn, 1953;Kumar et al, 1991;Basadur and Thompson, 1986). However, this is applicable under certain conditions (e.g.…”
Section: Quantitymentioning
confidence: 99%